Phase Equilibria in MeIMeIIIP2S6(Se6) Systems Which Include Quaternary Compounds (MeI - Cu, Ag; MeIII - In, Cr) - Potorij, M.V.; Hasinets, S.M.; Tovt, V.V.; Motrya, S.F.; Мilyan P.М. (Physics and Chemistry of Solid State, 2015)
The interactions of 6 quazibinary systems were investigated by methods of physical and chemical analysis in order to study the formation of solid solutions inside them. The character of interaction in these systems depending on various factors has been explained.